Biomarkers of epileptogenic zone defined by quantified stereo‐EEG analysis. Issue 2 (13th January 2014) - Gnatkovsky, Vadym; de, Marco; Pastori, Chiara; Cardinale, Francesco; Lo Russo, Giorgio; Mai, Roberto; Nobili, Lino; Sartori, Ivana; Tassi, Laura; Francione, Stefano
Summary Objective In one third of patients with a diagnosis of pharmacoresistant focal epilepsy who are candidates for therapeutic surgery, cerebral areas responsible for seizure generation can be defined exclusively with invasive intracranial recordings. A correct presurgical identification of the epileptogenic zone (EZ) with intracranial electrodes has a direct impact on postsurgical outcome. We aimed at identifying biomarkers of the EZ based on computer‐assisted inspection of intracranial electroencephalography (EEG). Methods Computer‐driven intracranial EEG analysis in the domains of time, frequency, and space was retrospectively applied to a population of 10 patients with focal epilepsy to detect EZ electrophysiologic markers. Next, a prospective study was performed on 14 surgery candidate patients. The stereo‐EEG computer‐assisted analysis of EZ boundaries performed blind from patients data was compared to that defined with the traditional visual inspection completed by neurophysiologists. Results In the retrospective study, the EZ was characterized by the combined detection of three biomarkers observed at seizure onset: (1) fast activity at 80–120 Hz associated with (2) very slow transient polarizing shift and (3) voltage depression (flattening). Correlations between these indexes were calculated for each seizure. In the prospective study, the quantified analysis based on the three biomarkers confirmed a complete overlap between leads within the EZ identified by expert clinicians. In 2 of 14 patients the proposed biomarkers partially identified the EZ. Significance Our findings demonstrate and validate with a prospective unbiased study the use of three neurophysiologic intracranial EEG parameters as excellent biomarkers of ictogenesis and as reliable indicators of EZ boundaries.